A retinal simulation study on the influence of spherical aberration, astigmatism and optotype on the Jackson cross cylinder test - Gargallo, Diana; García, Esther; Perches, Sara; Remón, Laura; Ares, Jorge (Journal of optometry, 2025)
To study how spherical High-Order Aberration (HOA), astigmatism levels (-0.75 D and -1.25 D), and optotype type (dot pattern vs. letter row) influence patients’ responses in identifying the cylinder axis orientation with the Jackson Cross Cylinder Technique (JCCT). Numerical simulations of retinal images corresponding to JCCT procedures were conducted and evaluated by 40 subjects. In order to do this, synthetic aberrometric profiles with and without HOAs (4th-order and 6th-order spherical aberrations) and two different astigmatism levels were generated from different Jackson Cross Cylinder axis positions and flips. The variable under study was the percentage of correct responses (hits) during each flip of the cross-cylinder lens. Statistical significance was assessed through confidence intervals overlapping evaluation. To achieve 90 % accuracy, the JCCT should begin by deviating >7.5° from the subject's astigmatism axis without spherical HOA and by >15° with them. The magnitude of astigmatism had minor relevance. The dot pattern was more accurate than the letters without HOAs; however, 72.5 % of observers considered that letter optotypes simplify the blur discrimination task. According to our simulation experiment for astigmatic axis selection with JCCT, the presence of spherical HOAs significantly impacts the accuracy of patient responses. The type of optotype and the magnitude of astigmatism did not exhibit a clear relationship with accuracy, except in the case of the dot pattern optotype in the absence of HOAs. Under these conditions, the dot pattern achieved the highest rate of accurate responses.